MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI MEDIA KARTU ANGKA DI KELOMPOK A KOBER ASSA’ADAH - Teti Nurhayati; Rohmalina Rohmalina (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2020)
The introduction of mathematical concepts is important for children to understand for further education, especially regarding numbers. Because numbers are always used in all activities. Introducing mathematics learning in AUD is done by playing and playing through number card media will be more interesting and children will be enthusiastic about participating in learning. So researchers are interested in researching with the title "Improving the Ability to Recognize the Number Symbols through the Number Card Media in Group A Kober Assa'adah". This study aims to improve the ability to recognize number symbols through the number of card media in group A Kober assa'adah. This research is a Classroom Action Research (CAR), with the subject of the study being 15 children from the Kober Assa'adah group, which consisted of 5 boys and 10 girls. Data obtained through observation, documentation, and interviews. Data analysis used descriptive analysis with a qualitative approach. With the results of the discussion, it can be concluded that recognizing child number symbols can be improved through the number of card media. The improvement in recognizing number symbols is done through various number card media with attractive colors so that children are interested in participating in the learning process to recognize numbers. Besides understanding numbers is the first step of mathematics, without understanding numbers, a child will have difficulty in the next learning phase. By using some card media the children are enthusiastic to take part in learning to recognize numbers. The results of the study of the ability of numbers through media card numbers increase and can be seen from the percentage of prasiklus 15%, cycle I 25%, and cycle II 68%.Pengenalan konsep matematika penting dipahami oleh anak untuk pengetahuan di jenjang pendidikan lebih lanjut, terlebih mengenai bilangan.  Mengenalkan pembelajaran matematika pada anak usia dini dilakukan dengan permainan media kartu angka sangat tepat dilakukan dalam meningkatkan kemampuan mengenal lambang bilangan.  Penelitian ini bertujuan untuk meningkatkan kemampuan mengenal lambang bilangan melalui media kartu angka di kelompok A Kober assa’adah. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK), dengan subjek penelitiannya 15 anak kelompok A Kober Assa’adah yang terdiri dari 5 Orang anak laki-laki dan 10 orang anak perempuan. Data diperoleh melalui observasi, dokumentasi dan wawancara. Analisis data memakai analisi deskriptif dengan pendekatan kualitatif.  Dengan hasil pembahasan, dapat disimpulkan bahwa mengenal lambang bilangan anak dapat ditingkatkan melalui media kartu angka. Peningkatan mengenal lambang bilangan dilakukan melalui media kartu angka yang bervariasi dengan warna- warna yang menarik, agar anak tertarik mengikuti proses pembelajaran mengenal bilangan. Selain itu memahami bilangan merupakan langkah awal dari pelajaran matematika, tanpa pemahaman akan bilangan, maka seorang anak akan mengalami kesulitan dalam tahapan pembelajaran selanjutnya. Dengan menggunakan media kartu angka anak- anak antusias untuk mengikuti pembelajaran mengenal bilangan. Hasil penelitian kemampuan bilangan melalui media kartu angka meningkat dan dapat dilihat dari prosentase prasiklus 15% , siklus I 25%, dan siklus II 68%.